Evaluating a Standardized Transition of Care Process for Pediatric Inflammatory Bowel Disease Patients - Jennifer Lynne Shearer; Sharon Perry; Nicole Lidyard; Carolyn Apperson-Hensen; Sarah DeLozier; Kimberly Burkhart; Jeffry Katz; Jonathan Moses (MDPI AG, 2020)
To reduce lapses in care for pediatric inflammatory bowel disease (IBD) patients approaching adulthood, a health maintenance transition visit (HMV) was developed to supplement standard medical care (SMV). Our aim was to assess the effect of the HMV on transition readiness. A retrospective chart review was conducted at a single center with demographics and clinical data from HMV and SMV visits. Effectiveness of the HMV was assessed by the patient health questionanaire-9 (PHQ-9) and transition readiness assessment questionnaire (TRAQ) scores. A total of 140 patients, 80% Caucasian and 59% male completed an HMV. The mean age was 18 ± 2 years old, and 93% of patients reported inactive or mild disease. Patients who completed at least 1 prior HMV scored significantly higher on the TRAQ when transferring to adult care compared to patients transferred at their first HMV visit (92 vs. 83, p < 0.05). Of patients with no prior depression diagnosis, 36% had a positive screen for depression. A significant relationship was identified between disease status and PHQ-9 (p < 0.05). This study demonstrated a structured HMV increased transition readiness and quantified the significant under-diagnosis of depression in this population, emphasizing the importance of screening. These results indicate depression may affect patients' transition preparedness.